RESEARCH IN EMERGENCY CARE–THERE'S AN APP FOR THAT!. Issue 10 (7th September 2013) - Crede, A; Roland, D; Alade, J; Bryceland, C; Lock, R; Coats, T
Abstract : Objectives & Background: Many emergency medicine clinical trials have struggled to recruit to 'time and target' with investigators having to make a large additional effort or extend the time for recruitment. This study was performed to describe our experience in the use of a computer 'app' to facilitate the process of research subject identification and communication between the ED staff and the research team. Key questions were: 1) Does the introduction of an iPad 'app' result in a greater rate of patient notification to the research team? 2) Which type of notification method was most used? Methods: An observational 'before and after' study was performed where ED staff had the choice of using a telephone 'research hotline', verbal notification, a sticky label on the clinical notes or an iPad app (in the second phase of the study). A 'gold standard' was provided by a manual search of the notes of every patient who presented to the ED. We developed the specification for an 'app' that presented the trial entry criteria coupled with an easy embedded method of emailing the research team using only three 'clicks'. The iPads were secured to walls in key locations (such as triage areas) and ED staff simply entered the patient's identification number and pressed 'send' for a message to be emailed. We reviewed the method of patient notification for 3 months before and after the introduction of the iPad system. Results: There was a significant (Fisher's Exact Test. p<0.0001) increase in 'real time' notification of patients to the research team from 18% to 33% after the introduction of the iPad app. The mode of notification also changed–with no use of the 'research hotline' telephone number after the app system was introduced. The use of sticky labels and the number of verbal notifications was also greatly reduced (See table 1). Conclusion: There was a significant increase in the immediacy of communication after the introduction of the iPad app. This occurred without a large amount of input from the research team, and seemed to be due to the staff knowing a specific location for the system and the ease of use, with the whole process taking less than 20 seconds. ED staff seemed to prefer using the 'app', as after it was introduced there was very little use of the well publicised 'research hotline' phone number. Information and communications technology can aid in the timely identification of potential research subjects in emergency care.